KETERSEDIAAN AIR KAWASAN TAMAN NASIONAL GUNUNG GEDE PANGRANGO (Water Availability in Gunung Gede Pangrango National Park Area) - Siti Badriyah Rushayati (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Gunung Gede Pangrango National Park (TNGP) has a role to supply the water for some towns for example Bogor, Cianjur, Sukabumi and Jakarta. In order to get water availability to continu, water resource conservation is needed. One of the basic data that is needed for water resource conservation Gunung Gede Pangrango National Park is potential to keep water. By the Methode of Water Balance (Thornthwaite and Mather, 1957), TNGP is potential to keep water is 548.960.480 m3/year. So that regulation of the use of water is needed. Use of water no more than potential to keep of water.Key words: water supply, water balance, national park.